Effect of Glycerol on the Activity of a-Chymotrypsin Encapsulated in Sol-Gel Derived Silica Monoliths - Sri Kunarti, Eko; Moran, Grainne (Asian Journal of Chemistry, 2011)
Preparation and properties of a biochemically active sol-gel monolith were investigated by encapsulating the enzyme a-chymotrypsin in a polymerizing tetramethoxysilane in presence of glycerol as an additive and pore forming template. The enzyme encapsulated in the templated mesoporous sol-gels exhibited an improvement in thermal stability and well behaved apparent catalytic activity, compared to those in non-templated microporous host, synthesized in the absence of glycerol. The apparent catalytic activity of encapsulated enzyme was closely associated with the concentration of template in as-synthesized sol-gels. This transparent, mechanically and chemically stable bioactive sol-gel glass may be used for the development of biochemical sensors and for the purpose of chemical catalysis.